Pancreatic panniculitis as the first manifestation of the pancreatic involvement during the course of a gastric adenocarcinoma - ALTINOK SÜT, PELİN; BEYAZIT, H.; Aydin, O.; DEMIRKESEN, C.; DERIN, D.; Sut, PELİN; EMRE, A.; MANDEL, N. (My University, 2011)
Pancreatic panniculitis (PP) is a rare disease presenting during the course of pancreatic diseases such as acute and chronic pancreatitis, pancreatic carcinoma. There are also a few reports of PP associated with other carcinomas. We present a 69-year-old male patient of gastric carcinoma with PP. The literature is reviewed, clinical and histological features of the case are discussed. This is the first case of PP in a gastric carcinoma patient reported in literature. As a conclusion, PP can be the first manifestation of a pancreatic metastasis of any carcinoma.